2023
DOI: 10.1021/acs.jpcc.2c08447
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Water-Forming Reaction on Graphite- and Ceria-Supported Palladium Nanoparticles and Nanoislands by the Work Function

Abstract: The water-forming reaction (WFR) between oxygen and hydrogen on metal surfaces is an important reaction in heterogeneous catalysis. Related research mostly focused on crystalline metal surfaces and thick films; however, supported nanoparticles (NP) have been rarely considered as well as a possible influence of the support on the NP catalytic activity. Here, we report on the WFR on graphite-supported palladium NPs and nanoislands (NI), which are characterized at room temperature and under ultrahigh vacuum condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…The work function (WF), a fundamental property of materials, is widely used to describe various surface chemical processes, including corrosion, friction, oxidation, and the attachment of molecules. , While limited studies have investigated the relationship between surface roughness and the gold work function, research on other metals has demonstrated the impact of surface roughness on the work function. Notably, metals like silver, , copper, and indium tin oxide (ITO) show a decrease in work function as surface roughness increases, whereas aluminum and magnesium exhibit the opposite trend.…”
Section: Introductionmentioning
confidence: 99%
“…The work function (WF), a fundamental property of materials, is widely used to describe various surface chemical processes, including corrosion, friction, oxidation, and the attachment of molecules. , While limited studies have investigated the relationship between surface roughness and the gold work function, research on other metals has demonstrated the impact of surface roughness on the work function. Notably, metals like silver, , copper, and indium tin oxide (ITO) show a decrease in work function as surface roughness increases, whereas aluminum and magnesium exhibit the opposite trend.…”
Section: Introductionmentioning
confidence: 99%